Dirtbag rapture - Sebela, Christopher; Sebela, Christopher; Goode, Kendall; Contreras, Gab (Oni-Lion Forge Publishing Group, LLC., 2022)
After a near-death experience, stoner Kat has the ability to see and hear ghosts as well as take them to locations of their choosing through her "mindscape." When she unwittingly takes part in a demonic plan to screw up the world, Kat is forced to take an active role in the epic battle between good and evil.